Kierkegaard and the Theology of the Nineteenth Century: The Paradox and the ‘Point of Contact’. By George Pattison.Kierkegaard and the Quest for Unambiguous Life: Between Romanticism and Modernism. Selected Essays. By George Pattison - Shakespeare, Steven (The journal of theological studies, 2013)
‘Kierkegaard is a writer of contradictions.’ So opens George Pattison’s exploration of Kierkegaard as a theologian of the nineteenth century. Kierkegaard certainly wears many literary masks to articulate the paradoxes of human existence before God. It is therefore striking to have two books published in close succession by one of the leading world Kierkegaardians, which so effectively articulate the tensions and ambiguities in the Danish writer’s work., Was Kierkegaard a God-fearing dogmatic theologian, or an arch-ironist, always seeking to outwit the age and have the laughter on his side? His works provide no direct answer: poetic, novelistic, and pseudonymous texts are published alongside sermon-like discourses and hyper-Christian invectives.